Morphological and palynological assessment of some taxa of genus Echinochloa through light and scanning electron microscopy. Issue 12 (5th August 2021) - Shaheen, Shabnum; Sharifi‐Rad, Javad; Harun, Nidaa; Khan, Muhammad Asaf; Ali, Muhammad; Khalid, Sana; Javad, Sumera; Hanif, Uzma; Sajjad, Sumera; Ahmad, Mushtaq; Sonia, Romisha; Khan, Farah
Abstract: The present study was undertaken to gather information on selected species of Echinochloa based on their morphological and palyonological examination through light and scanning electron microscopy. As the Echinochloa species are most problematic grass weeds and exhibit high interspecific and intraspecific variability so due to their great morphological diversity it is difficult to recognize them. A lot of variation was observed in morphological features of studied taxa. In the present study, E . colona had more or less spreading dense racemes whereas in E . crus‐galli racemes were linear to ovate. Upper glume surface was pubescent in E . colona, hispid in E . crus‐galli and spinose in E . walteri . E . colona was comprised of five‐nerved glumes whereas in E . crus‐galli glumes were three‐nerved. Although pollen basic characters in family Poaceae remains consistent but great variation was observed in pollen of studied taxa. The pollen size was quite variable among the species of genus Echinochloa . In polar view, the size of pollen grains ranged from 27.5 (20–35) μm to 40 (30–50) μm. E . crus‐galli was appeared to be the smallest in size whereas E . colona was the largest.). P/E ratio ranged from 0.84 to 1.15 μm among the species. The highest value of pollen fertility was found in E . colona as 93.33% and lowest was in E . crus‐galli as 87.50%. The morphological key of studied taxa is also given to study variations. In conclusion, it was observed that microscopy of morphological and palynological assessment can play a vital role in identification of taxonomically problematic taxa. Abstract : The morphological and palynological feature of Echinochloa taxa were observed through scanning electron microscopy. The morphological key of studied taxa is given to delimit the taxa. It was proven from the present study that there are a lot of variations in morphological as well as palynological traits among the studied Echinochloa taxa. This is the first morphological study of Echinochloa species along with the palynological parameters to study variation in this genus in Pakistan.